EFFORTS TO IMPROVE WOM’ TO ACHIEVE CONSUMER SATISFACTION BY IMPROVING SERQUAL AND PRICE POLICY IN THE HOTEL. “JANEVALLA” BANDUNG - Rachmawati, Mariana; Farenda, Raden Risky; Tanudjaja, Erik; Sinaga, Obsatar (CENTRAL ASIA AND THE CAUCASUS, 2022)
The object of this research is the Hotel. “Janevalla” Bandung, with the unit of research analysis being hotel consumers who have stayed there and know the hotel very well. "Janevalla", this hotel is located in a very strategic location in the city of Bandung, precisely on Jalan Merdeka and close to Mall Bandung Indah Plaza, this research was carried out in an effort to improve word of mouth for the achievement of consumer satisfaction by improving service quality and price policies at hotels . "Janevalla" Bandung, where the hypothesis test uses Phat Analysis, where the results of this study are that there is a significant influence between the creation of good word of mouth from consumers after consumers are satisfied with the quality of service and the price policy offered by the hotel. “Janevalla” Bandung